Approximate Estimation Methods for Exponential Rayleigh Distribution - AL-Sultany, Shurooq A.K.; Hussein, Lamyaa Khalid (Iraqi Journal of Science, 2025)
This paper introduces approximate estimators for the scale parameters, reliability, and hazard rate functions of the exponential Rayleigh distribution using Modified Maximum Likelihood and Bayesian method. The Modified Maximum Likelihood estimator requires iterative techniques such as the modified Newton–Raphson method due to the unavailability of closed-form expressions. Bayesian estimators are derived using both symmetric and asymmetric loss functions, and Lindley's approximation method is employed for integrals that lack closed-form solutions. Finally, the estimators obtained are compared through Monte Carlo simulation study.